ANALISIS PERBEDAAN PROFITABILITAS, TOTAL ASSET TURN OVER, KEBIJAKAN UTANG DAN KEBIJAKAN PEMBAGIAN DIVIDEN PADA PERUSAHAAN ROKOK, PERUSAHAAN KONTRUKSI DAN BANGUNAN SERTA PERUSAHAAN SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Firdaus, Rizqi Romadhani Ati; Widarno, Bambang; Harimurti, Fadjar (Universitas Slamet Riyadi, 2019)
The purpose of this study was to analyze the effect of profitability, total asset turnover and debt policy on dividend policy and to analyze differences in dividend policy in cigarette companies, construction and building companies and cement companies listed on the Indonesia Stock Exchange. This type of research is a case study. A sample of 18 cigarette companies, cement and construction and building companies are listed on the Indonesia Stock Exchange 2013 – 2016. Data collection techniques use documentation. Data analysis techniques use Desciptive test and Post Hoc test.. The results of shows that there is a difference ROA, TATO, debt policy and dividend policy in cigarette companies, construction and building companies and cement companies listed on the Indonesia Stock Exchange.